2020
DOI: 10.1038/s41598-020-77922-1
|View full text |Cite
|
Sign up to set email alerts
|

Actively tunable THz filter based on an electromagnetically induced transparency analog hybridized with a MEMS metamaterial

Abstract: Electromagnetically induced transparency (EIT) analogs in classical oscillator systems have been investigated due to their potential in optical applications such as nonlinear devices and the slow-light field. Metamaterials are good candidates that utilize EIT-like effects to regulate optical light. Here, an actively reconfigurable EIT metamaterial for controlling THz waves, which consists of a movable bar and a fixed wire pair, is numerically and experimentally proposed. By changing the distance between the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 60 publications
(55 reference statements)
0
38
0
Order By: Relevance
“…By applying voltage on the comb driver, a continuous lateral shifting between the coupled resonators can be induced to 20 µm. A MEMS integrated device is proposed by using EIT metamaterial, as shown in Figure 5e [84]. The comb driver design is composed of a fixed beam and a movable beam based on a silicon on insulator (SOI) wafer.…”
Section: Horizontal Tuning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By applying voltage on the comb driver, a continuous lateral shifting between the coupled resonators can be induced to 20 µm. A MEMS integrated device is proposed by using EIT metamaterial, as shown in Figure 5e [84]. The comb driver design is composed of a fixed beam and a movable beam based on a silicon on insulator (SOI) wafer.…”
Section: Horizontal Tuning Methodsmentioning
confidence: 99%
“…The geometry of integrated metamaterial is rapidly reduced, which means the MEMS-based metamaterial can be gradually operated from THz and IR, as well as visible spectra [90]. [80]; (b) schematic of the switchable magnetic metamaterial consisting of two semi-square split rings separated by a gap [81]; (c) schematics of the micromachined metamaterial with the element consisting of a two-cut SRR and two free-hanging slabs [82]; (d) schematic of the tunable metamaterials, including broadside-coupled SRRs (BC-SRRs) [83]; (e) schematic of the MEMS integrated device-unit cell of the EIT metamaterial consists of a cut wire and a wire pair [84]; (f) schematics of the tunable metasurface for the polarization conversion and the polarization rotation [85]; (g) schematics of polarization-sensitive IR metamaterials (PSIMs) [86]; (h-j) schematic of a tuning eSRR array by using comb drive horizontal tuning platforms [87][88][89].…”
Section: Horizontal Tuning Methodsmentioning
confidence: 99%
“…Moreover, many studies reported numerous microelectro-mechanical-system (MEMS) based metamaterial and metasurface structures for numerous applications [18][19][20][21][22]. Ma et al [18] developed polarization-sensitive MEMS-based tunable metamaterials for the terahertz spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The lens was made of MEMS and has an optical power shift of more than 4% per 1 µm movement of the metasurface. In 2020, Huang et al [22] developed an actively tunable THz filter based on MEMS metamaterial. Due to the advantage in optical applications, electromagnetically induced transparency (EIT) analogues in classical oscillator systems were also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the development of MM has been performed quickly and different kinds of MM were proposed, leading to many potential applications, such as MM perfect absorber [12,13], MM perfect lens [14,15], chiral MM [16,17] and MM wireless power transfer [18,19]. Besides the aforementioned applications, the EIT-MM also attracted great interest due to its simplicity in comparison with the original quantum systems [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%